Profiles of the Abilities of Preschool Aged Children in an Isolated Northern Community - Canning, Patricia (Canadian Journal of Education/Revue canadienne de l’éducation, 1991)
This preliminary investigation into cognitive abilities, social competence, and home environments of preschool children living in a northern Labrador commun- ity was a first step in the development of an appropriate preschool program. The preschool was intended to help alleviate a pattern of school failure in the community. Eighteen children ranging in age from 34 to 46 months performed on standardized tests of language and cognitive ability at levels suggesting they were at risk of school failure. Even within this sample there is a subgroup who are at even greater risk and who are not receiving any early intervention. On a test of social competence both groups scored above the normative mean. These findings have implications for preschool intervention and for early schooling. Cette recherche préliminaire axée sur les aptitudes intellectuelles, les aptitudes sociales et les milieux familiaux des enfants d'âge préscolaire d'une communauté du nord du Labrador a constitué la première étape de l'élaboration d'un programme préscolaire visant à contribuer à la diminution des échecs scolaires au sein de cette communauté. Les résultats des tests mesurant le langage et les aptitudes intellectuelles de 18 enfants âgés de 34 à 46 mois ont donné à penser que ces derniers risquaient d'échouer à l'école. Un sous-groupe encore plus susceptible d'échouer ne fait l'objet d'aucune intervention précoce. Dans un test portant sur les aptitudes sociales, les deux groupes ont obtenu des résultats supérieurs à la moyenne. Ces observations peuvent servir en matière d'intervention et d'éducation préscolaires.